Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific - Nielsen, Jørgen G.; Møller, Peter R.; Segonzac, Michel (Zootaxa, 2006)
A new genus and species of ophidiid fishes, Ventichthys biospeedoi, is described based on two male specimens caught in the French BIOSPEEDO expedition to the South East Pacific Rise. They were caught by a baited trap at the hydrothermal vent site Oasis (17°25.38’S, 113°12.29’W) at 2586 m. The new genus differs from all of the 48 known ophidiid genera by its thick skin, posteriorly placed and enlarged kidneys, broad head, and 4 lateral lines. The most similar genera are Benthocometes and Petrotyx having a blunt snout, one basibranchial tooth patch, granular teeth, and no free pectoral fin rays. Remarks on the ecology of the new species are based on analysis of video documents taken in situ by a submarine Nautile.